Vertical Variability in Bark Hydrology for Two Coniferous Tree Species - Ilek, Anna; Van Stan, John T.; Morkisz, Karolina; Kucza, Jarosław (Frontiers in Forests and Global Change, 2021)
As the outermost layer of stems and branches, the bark is exposed to the influence of atmospheric conditions, i.e., to changes in the air’s relative humidity and wetting during storms. The bark is involved in water interception by tree canopies and stemflow generation, but bark-water relations are often overlooked in ecohydrological research and insufficiently understood. Relative to other canopy ecohydrological processes, little is known about vertical variation in bark properties and their effect on bark hydrology. Thus, the objective of this study was to analyze changes in physical properties (thickness, outer to total bark thickness ratio, density, porosity) and hydrology (bark absorbability, bark water storage capacity, hygroscopicity) vertically along stems of Norway spruce (Picea abies (L.) Karst.) and silver fir (Abies alba Mill.) trees. Our null hypotheses were that bark hydrology is constant both with tree height and across measured physical bark properties. We found that bark thickness and the ratio of outer-to-total bark thickness decreased with tree height for both species, and this was accompanied by an increase in the bark water storage capacity. In contrast, the bark's density, porosity, and hygroscopicity remained relatively constant along stems. These results inform ecohydrological theory on water storage capacity, stemflow initiation, and the connection between the canopy water balance and organisms that colonize bark surfaces.